The Importance of Yogic Science for Humanity in Today’s Era - Aung Than, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
The escalating crises of the 21st century - psychological distress, ecological collapse, social fragmentation, lifestyle imbalance, and existential disorientation, underscore a significant disparity between swift technological advancement and the development of inner human consciousness, suggesting a crisis that transcends mere systems to touch upon the essence of consciousness itself. In this framework, yogic science, anchored in the Upanishads, the Bhagavad Gita, and Patanjali’s Yoga Sutras provides a thorough and practical approach to holistic human flourishing by merging physical health, mental regulation, ethical discipline, and spiritual insight.This study explores the philosophical underpinnings and contemporary significance of yogic science through a detailed analytical and interpretative review of classical Sanskrit texts in conjunction with modern research in psychology, neuroscience, and preventive healthcare. It illustrates how yogic principles such as equanimity, disciplined action, ethical conduct, and self-awareness effectively tackle the fundamental causes of contemporary suffering while resonating with modern notions of emotional regulation, resilience, and wellbeing. Backed by citations from Sanskrit verses, thematic charts, and conceptual frameworks, the analysis emphasizes yogic science as a preventive and transformative human science with considerable potential for incorporation into education, healthcare, environmental ethics, and public policy, thereby providing sustainable avenues for both individual and global wellbeing.
Keywords: Yoga; Gita; Upanishad; Patanjali Yoga Sutra; Healthcare; Education